Biochemical changes of rice genotypes against blast (Magnaporthe oryzae) disease and SSR marker validation for resistance genes - Yasmin, Israt; Adhikary, Sourav; Hassan, Lutful; Sagor, G.H.M. (Journal of Phytology, 2023)
Rice blast caused by Magnoporthe oryzae is a major devastating fungal disease and represents a potential threat to world rice productions. However, information about the genetic and biochemical basis of disease tolerance is still limited. In this study, we tested the presence and diversity of resistant R genes using SSR markers, and the antioxidant enzymes catalase (CAT), ascorbate peroxidise (APX) and guaicol peroxidise (POD), activity and also the concentration of hydrogen peroxide (H2O2) and malondialdehyde (MDA) in resistant (BAUdhan 3) and susceptible (BRRIdhan 28) genotype. Molecular marker analysis reveals the presence of all ten studied resistant genes in BAUdhan 3. Among the markers studied, three markers namely RM224, RM72 and RM206 produce distinct band only in resistant genotype BAUdhan 3, which might be used to screen resistant genotypes. The enzymatic activity of APX, CAT and POD increased in the inoculated plant for both cultivars but the increase was more prominent for BAUdhan 3. The M. oryzae infections significantly increased the H2O2 content in BRRIdhan 28 and not much changed in BAUdhan 3. The MDA concentration was higher in the leaves of inoculated plants of BRRIdhan 28. The higher activities of APX and POD in the leaves of the inoculated plants of BAUdhan 3 resulted in lower H2O2 accumulation which can minimize the cellular damages possibly caused by reactive oxygen species. The result shows that the presence of more resistance genes and an effective antioxidative system in BAUdhan 3, which limits the damage caused due to fungal infection and thus contributes to greater resistance.